2013
DOI: 10.1891/0739-6686.31.327
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Cancer

Abstract: There are an estimated 13.7 million cancer survivors in the United States. Persistent and late effects of cancer therapy have contributed to an increased risk for co-morbid illness and higher all-cause mortality. Physical exercise is a targeted rehabilitative intervention following cancer therapy and a health promotion risk reduction intervention for patients as they transition into survivorship. This chapter provides a brief overview of the research on exercise and cancer survivor outcomes with a specific foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…This study showed a modest magnitude of the effect of exercise in eight studies, suggesting that longer interventions may have lasting effects. Another systematic review by Knobf and Winters‐Stone () included 17 RCT aimed at determining the impact of moderate exercise (walking) in patients with cancer. The trials demonstrated preservation of bone and maintenance of weight in the intervention group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed a modest magnitude of the effect of exercise in eight studies, suggesting that longer interventions may have lasting effects. Another systematic review by Knobf and Winters‐Stone () included 17 RCT aimed at determining the impact of moderate exercise (walking) in patients with cancer. The trials demonstrated preservation of bone and maintenance of weight in the intervention group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The trials demonstrated preservation of bone and maintenance of weight in the intervention group compared with the control group. This review may be unique, considering that many patients with cancer are prescribed bed rest (Knobf & Winters‐Stone, ). Knobf and Winters‐Stone () found that older patients who walked were discharged earlier compared with those who did not exercise, similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Although the vast number of studies in healthy populations indicate that, whereas caloric restriction is key to promoting weight loss, exercise and behavioral counseling to promote and support behavior change also are required to maintain weight loss long term; however, data are limited in cancer populations. Studies by Goodwin et al and others support the role that exercise plays in predicting weight loss at 1‐year follow up in cancer populations, and increased physical activity is recommended as an essential part of weight management in cancer survivors as it is for the general population. The need for exercise, however, may be particularly important for individuals with cancer, because there is sparse but concerning evidence that weight loss independent of exercise (especially resistance training) may promote sarcopenia or the loss of lean mass in an already compromised patient population.…”
Section: What Are the Current Guidelines?mentioning
confidence: 99%
“…Despite the importance of angiogenesis, there has been little research on the relationship between cancer and exercise in terms of angiogenesis. While the effects can vary according to the type of cancer, exercise is effective in alleviating cancer 45 , 46 . A consideration of the mechanisms of cancer and exercise in terms of angiogenic factors indicates that both may induce angiogenesis, which contradicts the view that the effects of cancer are lessened by exercise 47 , 48 .…”
Section: Introductionmentioning
confidence: 99%